SURGICAL LASERS: A REVIEW OF APPLICATIONS IN THE THERAPY OF ORAL MUCOSA LESIONS - Agop-Forna Doriana; Mihai Constantin; Forna Norina (Romanian Society of Oral Rehabilitation, 2020)
In this review are presented literature data collected from a Medline search, regarding the applications of surgical lasers in minor oral surgery. The search of literature data was performed for studies published between 2007 and 2019, regarding the use of lasers in the removal of oral benign mucosa lesions, treatment of oral premalignant lesions and the therapy of oral vascular lesions.